Luminous restriction and chemical control with glyphosate in integrated management of Urochloa brizantha L. (Research, Society and Development, 2022)
The objective was to evaluate the effect of different light conditions in the cultivation environment on the control of U. brizantha by glyphosate. The experimental design was in a plot scheme divided into randomized blocks with five replications. In the plots, environments with light conditions were allocated: full sun, intermittent shading with 3 hours of sun/day, and continuous shading. In the subplots, the herbicide doses: 0, 480, 960, and 1440 g. a. e. glyphosate ha-1 applied to U. brizantha plants. The control of U. brizantha by the herbicide glyphosate was more efficient in shaded environments, either with continuous or intermittent shading, in relation to full sun, indicating that the conditions of light influenced the action of the herbicide. At 35 DAA, control values of U. brizantha above 80% were observed from the 765 g. a. e ha-1 dose of glyphosate for treatments with shading. Already in conditions of full sun, 65% of control values were reached in the highest dose, which is considered unsatisfactory for the management of this species. U. brizantha submitted to light restriction had the content of epicuticular wax, starch, soluble and total sugar reduced; however, the leaf area was larger in these environments compared to full sun. The reserve content, epicuticular wax, and leaf area variables are affected by shading with a direct relationship with the greater control of U. brizantha by glyphosate in this cultivation condition.